Numerical Calculations on the Unsteady Aerodynamic Force of the Tilt-Rotor Aircraft in Conversion Mode - Hao Chen (International Journal of Aerospace Engineering)
A computational method is developed in order to predict the unsteady aerodynamic characteristics of the tilt-rotor aircraft in conversion mode. In this approach, the rotor is modeled as an actuator disk so that the effect of individual blades can be ignored. A novel predictor-corrector-based dynamic mesh method is presented for dealing with extremely large mesh deformation during a conversion process. The dual time-stepping approach and the finite volume scheme are applied to solve the unsteady N-S equation. A parallel algorithm is utilized in this work to improve the computational efficiency. By using the present method, quantitative and qualitative comparisons are made between the aerodynamic coefficients obtained in the quasi-steady fixed conversion mode and the time-accurate continuous transition flight condition. Both two-dimensional (2D) and three-dimensional (3D) computations are carried out. The influence of the tilt modes and the tilt period time on the unsteady aerodynamic forces are also studied. Numerical results demonstrate that the developed method is effective in simulating the aerodynamic characteristics of the tilt-rotor aircraft in conversion mode.